2022
DOI: 10.15547/bjvm.2020-0091
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian and uterine haemodynamics and their relation to steroid hormonal levels in postpartum Egyptian buffaloes

Abstract: The current study aimed to assess the ovarian and uterine haemodynamics in postpartum (pp) Egyptian buffaloes and their relation to steroid hormonal levels (progesterone and estrogen). Six multiparous buffalos with normal calving were examined by using trans-rectal Doppler sonography to assess the blood flow in ipsilateral and contralateral ovarian and uterine arteries. Doppler parameters viz. peak systolic velocity (PSV), blood flow volume (BFV), resistance (RI) and pulsatility index (PI) were measured at 1st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…The higher estradiol concentration in the FP, as described in this study, may explain the increase in ovarian blood perfusion. Recent studies reported that a strong correlation exists between estradiol (E2), a potent vasodilator, and ovarian blood flow (OBF) [47,56]. Moreover, an OBF increase was noted after the treatment of postpartum ewes with estradiol 17β [57] .…”
Section: Discussionmentioning
confidence: 99%
“…The higher estradiol concentration in the FP, as described in this study, may explain the increase in ovarian blood perfusion. Recent studies reported that a strong correlation exists between estradiol (E2), a potent vasodilator, and ovarian blood flow (OBF) [47,56]. Moreover, an OBF increase was noted after the treatment of postpartum ewes with estradiol 17β [57] .…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of estradiol‐17 β (pg/ml; E2, EIA‐2693) and progesterone (ng/ml; P4, EIA‐1561) were analysed using DRG diagnostics (DRG, Germany, RUO in the USA) via competitive ELISA, with a sensitivity of 9.714 pg/ml, 0.045 ng/ml, respectively. The intra‐assay CVs for E2 and P4 were 5.4% and 6.81%, respectively (EL‐Sherbiny, EL‐Shahat, et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Uterine arteries' blood flow (UBF) controls placental functions and thickness and subsequently foetal well‐being (Elmetwally et al, 2021). Evaluation of uterine haemodynamics using Doppler ultrasonography has been considered a noninvasive, reliable and accurate tool, providing an insight into the placental and foetal status (EL‐Sherbiny, EL‐Shahat, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Progesterone (P4, EIA-1561) was analyzed using ELISA kits (DRG, Germany) by competitive assaying with inter and intra assays precisions of 9.96 and 5.4, respectively, and test sensitivity of 0.045 ng/ml. Serum samples were used in assaying the nitric oxide (NO) via its metabolites (NOMs; μmol/L) as previously examined in our laboratory ( 40 , 41 ). The nitric oxide inter and intra assay coefficients were 1.17% and 1.09%.…”
Section: Methodsmentioning
confidence: 99%